Minimally invasive surfactant therapy versus intubation for surfactant administration in very low birth weight infants with respiratory distress syndrome - Xing-An Wang; Lih-Ju Chen; Shan-Ming Chen; Pen-Hua Su; Jia-Yuh Chen (Pediatrics and Neonatology)
Background: Minimally invasive surfactant therapy (MIST) is a new mode of surfactant administration without intubation to spontaneously breathing preterm infants with respiratory distress syndrome (RDS). The aims of this study were to assess the feasibility, efficacy and safety of using MIST to give surfactant for very low birth weight (VLBW) infants with RDS. Methods: In total, 53 VLBW infants who were born before 32 gestational weeks with spontaneous breathing, respiratory distress, and requiring surfactant therapy were divided into two groups. The infants in group A (n = 29) were intubated and received surfactant replacement therapy via endotracheal tube, followed by mechanical ventilation (MV). The infants in group B (n = 24) received tracheal instillation of surfactant via a semirigid vascular catheter during spontaneous breathing under nasal continuous positive airway pressure (nCPAP). After surfactant instillation, the infants in group B were still placed on nCPAP. Results: Our data showed that infants in group B (MIST group) had significantly lower rate (P < 0.05) of composite outcome of death or bronchopulmonary dysplasia (BPD), duration of intermittent positive airway pressure ventilation (IPPV) or MV, drug treatment of patent ductus arteriosus (PDA), and surgical ligation of PDA than group A. Conclusion: MIST is feasible, safe and it may reduce the composite outcome of death or BPD for VLBW infants with RDS requiring surfactant replacement therapy. Key Words: bronchopulmonary dysplasia, minimally invasive surfactant therapy, respiratory distress syndrome, surfactant